Mahdis and millenarians: Shi'ite extremists in early Muslim Iraq - Tucker, William F. (Cambridge University Press, 2008)
Mahdis and Millenarians is a discussion of Shiite groups in eighth- and ninth-century Iraq and Iran, whose ideas reflected a mixture of indigenous non-Muslim religious teachings and practices in Iraq in the early centuries of Islamic rule. It demonstrates the period's fluidity of religious boundaries. Particular attention is given to the millenarian expectations and the revolutionary political activities of these sects. Specifically, it seeks to define the term 'millenarian', to explain how these groups reflect that definition, and to show how they need to be seen in a much larger context than Shiite or even Muslim history. The author concentrates, therefore, on the historical-sociological role of these movements. The thesis of the study is that they were the first revolutionary chiliastic groups in Islamic history and, combined with the later influence of some of their doctrines, contributed to the teachings of a number of subsequent Shiite or quasi-Shiite sectarian groups.